Corporate Risk, Cost Shifting, and Tax Avoidance - I Nyoman Agus Wijaya; Enny Prayogo; Rini Handayani; Ivan Prihartono (Universitas Kristen Maranatha, 2021)
Abstract This study aims to investigate relationship between corporate risk, cost shifting, and tax avoidance. Using 50 companies of all manufacturing companies listed in Indonesian Stock Exchange, we try to investigate a corporate risk, cost shifting and tax avoidance in annual report audited over long time periods (5 years) sequentially. Then, we test the relationship between corporate risk and cost shifting to tax avoidance that reduced the firm’s income tax payments. This study provides evidence that companies with high risk are more likely to do tax avoidance and companies that have a good strategy in allocating their costs are driven by the behavior of minimazing tax payments. We also find that the higher of corporate risk will increase corporate tax payment to Internal Revenue Services. Keywords: Corporate Risk, Cost Shifting, and Tax Avoidance